2020
DOI: 10.3390/ijms21197013
|View full text |Cite
|
Sign up to set email alerts
|

Ethionamide Preconditioning Enhances the Proliferation and Migration of Human Wharton’s Jelly-Derived Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are a useful source for cell-based therapy of a variety of immune-mediated diseases, including neurodegenerative disorders. However, poor migration ability and survival rate of MSCs after brain transplantation hinder the therapeutic effects in the disease microenvironment. Therefore, we attempted to use a preconditioning strategy with pharmacological agents to improve the cell proliferation and migration of MSCs. In this study, we identified ethionamide via the screening of a drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Human MSCs were expanded in media containing minimal essential alpha 1x medium (MEMα1x; Gibco, Waltham, MA, USA), 10% fetal bovine serum (FBS; Biowest, Riverside, MO, USA), and 0.5% gentamicin (Gibco, Waltham, MA, USA) at 37°C in a 5% CO2 incubator. As reported previously 25 , we applied a preconditioning protocol by treating hMSCs with ethionamide prior to transplantation to enhance the overall therapeutic efficacy of hMSCs. To prepare cells for transplantation, preconditioned hMSCs were harvested using 0.25% Trypsin-Ethylenediaminetetraacetic acid (EDTA) (Gibco, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Human MSCs were expanded in media containing minimal essential alpha 1x medium (MEMα1x; Gibco, Waltham, MA, USA), 10% fetal bovine serum (FBS; Biowest, Riverside, MO, USA), and 0.5% gentamicin (Gibco, Waltham, MA, USA) at 37°C in a 5% CO2 incubator. As reported previously 25 , we applied a preconditioning protocol by treating hMSCs with ethionamide prior to transplantation to enhance the overall therapeutic efficacy of hMSCs. To prepare cells for transplantation, preconditioned hMSCs were harvested using 0.25% Trypsin-Ethylenediaminetetraacetic acid (EDTA) (Gibco, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Observations were made up to 24 h in this study because fever subsided after 24 h in the clinical trial. Furthermore, according to studies that we have published recently, very few residual human MSCs were identified in the mouse brain one week following MSC transplantation [16,31,32]. Thus, although not extensively studied, since very few residual human MSCs were present in the mouse brain, signs of inflammatory responses may not have been detected at 1 or even 2 weeks following MSC transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al [ 44 ] have demonstrated that MSCs with enhanced proliferation and migration due to ethionamide were retained longer when injected into mouse brain and were expected to show better therapeutic effect than naïve MSCs in the treatment of brain diseases. Therefore, WJ-MSCs with enhanced proliferation and migration, due to high expression of AURKA, probably showed improved apoptotic effect in the mdx mouse due to the higher number of WJ-MSCs retained in the muscle tissue than the WJ-MSCs with low expression of AURKA.…”
Section: Discussionmentioning
confidence: 99%